STRATEGI PROMOSI LOYALTY PROGRAM MY PERTAMINA YANG DILAKUKAN OLEH PT PERTAMINA (PERSERO) TAHUN 2018 - Gina Salsabila Heryadi (Universitas Mercu Buana, 2019)
Marketing is currently growing rapidly. Promotion is very important to market a product so that customers know that the product is worth buying. A mature strategy is needed to promote a product. promotion strategies for successfully marketing company products to the public quickly and on target. Based on this, the authors focus on research, namely